Digital infrared thermal imaging of body and hoof skin surface temperature profile in Murrah buffaloes (Bubalus bubalis): A preliminary report - Siddalingaiah, Lokesh Babu Dyapasandra; Jeyakumar, Sakthivel; Manimaran, Ayyasamy; Pushpadass, Heartwin Amaladas; Sivaram, Muniyandi; Sathiyabarathi, Mayilsamy; Kumaresan, Arumugam; Kataktalware, Mukund Amritrao; Ramesha, Kerekoppa Puttaiah (Buffalo Bulletin, 2022)
The aim of the present study was to generate thermographic profile of foot region viz. body temperature (BTºC), coronary band temperature (CBTºC), hoof skin surface temperature (HSSTºC) and mean temperature difference (ΔTºC) in Murrah buffaloes (Bubalus bubalis) and its relation with ambient temperature. A total of 60 hooves of lactating Murrah buffaloes (n = 15) maintained in a farm, were monitored once a day continuously for 15 days before evening milking using forward-looking infrared (FLIR) i5 camera. Total of 1125 thermograms were analyzed using FLIR Quick Report 1.2 image analysis software. The mean ± SD (°C) of BT, CBT, HSST and ΔT of all animals throughout the experimental period were 37.39±0.05, 34.93±0.13, 34.16±0.13 and 0.76±0.26 respectively. The CBT was around 0.5 to 1°C higher than HSST. Statistical analysis revealed that ambient temperature is highly and positively correlated with CBT (ºC) (r = 0.95) and HSST (ºC) (r = 0.99), indicating greater influence of ambient temperature on surface temperature of foot region. Therefore, CBT (ºC) and HSST (ºC) have a tendency to follow variations in ambient temperature (R2 = 0.91 and 0.98 respectively). However, significant difference was observed between BT vs. CBT, BT vs. HSST and CBT vs. HSST (ºC). The mean ± SD (°C) of ΔT of all animals, throughout the observation period was 0.96±0.41. A significant difference was observed in ΔT between animals (P<0.001). However, significant difference was not observed in ΔT between days and among four hooves within animal. It is concluded that, to the best of our knowledge this is the first report on baseline thermographic information on BT, CBT, HSST and ΔT differentials for buffalo and its clinical significance in monitoring hoof health and management.